ANALISIS PENGARUH KUALITAS PELAYANAN, PROMOSI DAN LOKASI TERHADAP KEPUASAN KONSUMEN (Studi Kasus Pada PT. Maharani Tri Utama Mandiri Cabang Semarang) - Nurhanifah, Anik; Sutopo, Sutopo (Diponegoro Journal of Management, 2014)
The  aim  of  this  study  was  to  know  wether  the    sevice  quality,  location,  andpromotion  to  customers  satisfaction  of  PT.  Maharani  Tri  Utama  Mandiri  Semarang Branch. And analizing the predominant factor in influencing the customers satisfaction at PT. Maharani Tri Utama Mandiri Semarang Branch. This search sample amount of 75 respondents using as the sample by Purposive Sampling technique, ( is sampling based on a specific target , while the criteria that will be used is prospective migrants who are in the Training Center ( BLK ) PT . Maharani Tri Utama Mandiri Semarang branch independently at least one month .Based on the result of the study, it was found the regression equation as follows: Y = 0,414X1 + 0,159 X2 + 0,340X3The most powerful dependent variable was the   quality service (0,414) and were followed  by  location         (0,340),  and  the  last  variable  promotion  that  (0,159).  The hypothesis testing using t-test showed thatthere is one variable tgat is not significant is the variable promotion and two variable (quality service and location) have the positive and statistically significant impact to the dependent variable customer satisfaction. Figures adjusted R square of 0,647 indicates that 64,7 percent of the customer satisfaction could be explained by quality  service, promotion and location variables, meanwhile 35,3  percent of the rest were the impact of the other variable which not examined in this study.